Total neoadjuvant therapy followed by total mesorectal excision for rectal cancer in older patients real world data and proof of concept - Montroni, Isacco; Di Candido, Francesca; Taffurelli, Giovanni; Tamberi, Stefano; Grassi, Elisa; Corbelli, Jody; Mauro, Floranna; Raggi, Enrico; Garutti, Anna; Ugolini, Giampaolo (Frontiers in Surgery, 2024)
BackgroundRectal cancer (RC) commonly affects older patients. Total Neoadjuvant Therapy (TNT) has been introduced to improve local and systemic control of RC. The aim was to present real-world data of older patients receiving TNT followed by surgery after a frailty assessment and verify feasibility and safety of this approach.MethodsThis was a single-center retrospective study which enrolled all patients ≥70 years of age with RC who underwent TNT followed by surgery between November 2017 and April 2022. Data regarding cancer characteristics, neoadjuvant chemoradiotherapy (CRT), and toxicity were recorded. All patients underwent surgery 12–16 weeks after the end of therapy. Intra- and postoperative outcomes were recorded. Pre- and postoperative functional evaluation was carried out.ResultsFifteen patients were enrolled. Mean age was 74 (70–81) years. Mean distance of the tumor from the anal verge was 5.2 cm. Fourteen patients had positive nodes (93.3%), 11 (73.3%) showed involvement of the circumferential margin (CRM+) and 10 (66.6%) had extramural vascular invasion (EMVI+). Ten patients (66.6%) received mFOLFOX-6 and 5 CAPOX (33.3%) followed by CRT. After CRT, positive nodes were reported in 4 cases (26.6%), CRM+ in 4 (26.6%), and EMVI+ in 1 (6.6%). Transanal total mesorectal excision (taTME) was performed in all cases. Median operative time was 280 min (110–420). Median length of stay was 4 days (3–29). One Clavien-Dindo grade 4 complication, no readmissions, and no variations in pre- and postoperative functional status within 30 days from surgery were reported. No positive distal or CRMs were detected. Three pathologic complete responses were reported (20%).ConclusionsTNT followed by TME is feasible and safe in older patients, with good clinical and oncologic outcomes. Patient evaluation is crucial for maximizing cancer care in fit older patients.